Primary care for people with a newly diagnosed dementia in hospital after discharge. (20th December 2022) - Hegerath, Flora‐Marie; Giehl, Chantal; Otte, Ina; Vollmar, Horst Christian
Abstract: Background: Older people with cognitive impairment usually live at home. Possible deficits can be compensated there, often with the help of relatives. Therefore, the diagnosis of dementia is often delayed. It can lead to a first dementia diagnosis being made during an acute hospital stay. As a result, hospital discharge and subsequent care pose challenges for those involved. The aim of this study was to assess existing barriers and facilitating factors in the care of patients with a newly diagnosed dementia after hospitalization in the general practitioner (GP) setting. The study is funded by the German Alzheimer Society. Method: Sixteen semi‐structured interviews with GPs from Germany were conducted from July to December 2021. Data were analysed according to the qualitative content analysis from Kuckartz. Result: Theoretical saturation regarding the research question was reached within the qualitative interviews. The analysis showed that GPs identify communication deficits on the part of the hospitals as a barrier to provide adequate care for their patients. A conversation is rarely initiated with the GPs to ensure continued outpatient care. GPs use different strategies to provide care for their patients. Special importance is given to the communication with people with dementia and their relatives in a first consultation after hospital discharge to obtain detailed information, e.g., about the hospital stay or third‐party anamnesis. This first consultation is focused on organizing the care of patients in their own homes. Managing medication from the hospital is a critical issue for GPs, as patients are often prescribed many new medications. Conclusion: Since the acute reason for hospitalization is not dementia, there is usually no comprehensive assessment. It is therefore important for those affected that the diagnosis is verified after discharge and that appropriate measures are initiated. Based on the study results, practice‐oriented recommendations for the GP setting are going to be developed, which, for example, highlight the sensitive communication with those involved. For better initial care of their patients, GPs need adequate communication from the side of the hospital. Here, additional professional groups (e.g., care managers) and better digital networking can have a positive impact on care.